INteractive Virtual Expert-Led Skills Training: A Multi-Modal Curriculum for Medical Trainees - Curtin, Michelle; Downs, Jennifer; Hunt, Amber; Coleman, Emily R.; Enneking, Brett A.; McNally Keehn, Rebecca (Frontiers in Psychiatry, 2021)
Introduction: Internationally, pediatric depression and suicide are significant issues. Additionally, in the context of the COVID-19 pandemic, pediatric mental health needs are rising astronomically. In light of Child & Adolescent Psychiatrist (CAP) subspecialist shortages in the United States (US), there is an increasing call for primary care physicians in Family Medicine and Pediatrics to address an increasingly broad variety of patient needs. Here we report on the development and preliminary evaluation of medical student and resident perceptions on the “INteractive Virtual Expert-led Skills Training” (INVEST) medical education curriculum, a virtual synchronous CAP curriculum employing active learning strategies, including expert-led discussion and video modeling, and discussion designed to meet those priorities. Methods: In a standardized 60-minute training format, our curriculum leverages audience response system polling, video modeling of key clinical skills, and interactive discussion with an expert subspecialist, over a virtual video conferencing platform. The primary educational strategy relies on use of video modeling to demonstrate best practice with CAP led group discussion to solidify and explain important concepts. Five waves of medical students and residents (N=149) participated in the INVEST curriculum and completed pre- and post-training surveys regarding knowledge and comfort in the management of pediatric patients with depression and suicidality. Results: Trainee participants reported significant positive gains in perceived likelihood of encountering pediatric suicidality as well as knowledge/comfort with depression screening and suicidality assessment in a primary care setting. Across some competency areas, there was an effect of medical learner level. Learners at lower levels generally reported the highest benefit. Medical students reported significant increases in their comfort interpreting and discussing positive depression screens and evidenced the greatest relative benefit in comfort with discussing suicidality. Conclusion: To our knowledge, INVEST is the first fully virtual, multimodal curriculum led by expert CAP subspecialists. Our findings suggest that INVEST shows promise for equipping medical learners with baseline knowledge for caring for patients with pediatric depression and suicidality. This synchronous, virtually delivered curriculum allows for critical training delivered to diverse medical learners regardless of geographic location, a particular benefit during the current COVID-19 pandemic.